2016
DOI: 10.23860/dignity.2016.01.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Readiness to Exit Commercial Sexual Exploitation Among Women in India and the U.S.

Abstract: Exiting commercial sexual exploitation (CSE) is a difficult and prolonged process. This study examines the predictors of readiness to exit CSE, using the stages of change model as an underlying framework, among women in India (n=163) and the U.S. (n=87). Constructs such as years of schooling, residence, unemployment, age of entry, causes of entry, types of exploitation, addictions, presence of perpetrator, culture -individualistic and collectivistic, stigma, social support, empowerment, and current involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
4
0
1
Order By: Relevance
“…This would ensure that the individual is independent, with access to equal opportunities, and will not be further exploited. This also addresses pre-entry factors such as childhood abuse, addictions and lack of education (Belcher and Herr, 2005; Kramer and Berg, 2003), which make the individual not only vulnerable to entering the sex industry but also remaining enslaved (Wilson and Nochajski, 2016). The use of the harm reduction approach in the United States (Davis, 2000; Hotaling et al, 2003), as a way to encourage women to participate in the recovery process and facilitate their exit, stems from the belief that change occurs gradually (Dalla, 2006; Oselin, 2009), and the decision rests upon them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would ensure that the individual is independent, with access to equal opportunities, and will not be further exploited. This also addresses pre-entry factors such as childhood abuse, addictions and lack of education (Belcher and Herr, 2005; Kramer and Berg, 2003), which make the individual not only vulnerable to entering the sex industry but also remaining enslaved (Wilson and Nochajski, 2016). The use of the harm reduction approach in the United States (Davis, 2000; Hotaling et al, 2003), as a way to encourage women to participate in the recovery process and facilitate their exit, stems from the belief that change occurs gradually (Dalla, 2006; Oselin, 2009), and the decision rests upon them.…”
Section: Discussionmentioning
confidence: 99%
“…In India, the most important aspect of service provision was to economically empower the women, as that would address pre-entry factors such as poor economic conditions, runaway behaviour, lack of education and support, and gender discrimination (Vindhya and Dev, 2011), all of which lead women into and trap them in the sex industry (Wilson and Nochajski, 2016). Agency services were aimed not only at the woman, but also at the various stakeholders in her life, such as family members or partners abusing her, with the intention of preventing such interfamilial abuse, as breaking away from the collective is not a favourable option for most within such societies (Triandis and Suh, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies also identified several factors that enable people to leave trafficking, including spirituality, which provides a sense of hope and the motivation to escape (Hickle, 2017), social support (Wilson & Nochajski, 2016), social awareness programs on trafficking (Crawford & Kaufman, 2008), and access to economic empowerment programs for victims (Ferrari, 2016). Traffickers in turn use different strategies to control their victims, including, but not limited to, isolating, humiliating, and assaulting victims (Baldwin et al, 2015), and issuing or carrying out threats of violence against the victims and their family members (Kim, 2007).…”
Section: Trafficking Of Nigeriansmentioning
confidence: 99%
“…Einnig hafa þolendur vaendis upplifað að fá ekki aðstoð því þau uppfylli ekki þaer kröfur sem gerðar eru, eins og að hverfa tafarlaust úr vaendi eða haetta neyslu vímuefna (Neale & Hodges 2020). Þegar viðeigandi þjónusta er til staðar og veitt á réttum forsendum þá eru þolendur vaendis líklegri til þess að hverfa úr vaendi (Wilson & Nochajski 2016).…”
Section: Bakgrunnur Fólks í Vaendi Afleiðingar þEss Og úRraeði Til úT...unclassified